1984
DOI: 10.1128/mcb.4.11.2253
|View full text |Cite
|
Sign up to set email alerts
|

The minimum amount of homology required for homologous recombination in mammalian cells.

Abstract: Although DNA sequence homology is believed to be a prerequisite for homologous recombination events in procaryotes and eucaryotes, no systematic study has been done on the minimum amount of homology required for homologous recombination in mammalian cells. We have used simian virus 40-pBR322 hybrid plasmids constructed in vitro as substrates to Tn3 (9, 24), also catalyze recombination events between specific sites containing small regions of homology. The integration and excision of lambdoid phages (15) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
168
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(188 citation statements)
references
References 44 publications
18
168
1
1
Order By: Relevance
“…These studies also challenge the notion of minimum pairing segments of uninterrupted homology required for such exchanges (38)(39)(40). Finally, direct comparisons of germ-line mutation rates and population frequencies can provide insights into historical levels of selection operating in human populations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also challenge the notion of minimum pairing segments of uninterrupted homology required for such exchanges (38)(39)(40). Finally, direct comparisons of germ-line mutation rates and population frequencies can provide insights into historical levels of selection operating in human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Illegitimate recombination and the origin of satDNA Â satDNA junctions In mammals and plants, in vivo and in vitro experiments showed that efficient recombination between sequences requires a minimum of approximately 200 bp of uninterrupted homology (Rubnitz and Subramani, 1984;Opperman et al, 2004). Below this threshold, sequence divergence has an inhibitory effect on homologous recombination and can decrease threefold with a divergence level as low as 0.16%.…”
Section: Discussionmentioning
confidence: 99%
“…It was established that at least 50-to 100-bp homology is required for it (see, e.g., refs. [5][6][7]. This ensures that the fragments belong to 2 alleles of the same gene rather than to different genes.…”
Section: Homology Recognition Enigmamentioning
confidence: 99%